Fraud in the Savings and Loan Industry in California, Florida, Texas, and Washington, DC: White-Collar Crime and Government Response, 1986-1993 - Pontell, Henry N. ([Verlag nicht ermittelbar], 1999)
The purpose of this study was to gain an understanding of the factors that contributed to the epidemic of fraud in the savings and loan ("thrift") industry, the role that white-collar crime played, and the government response to this crisis. The researchers sought to describe the magnitude, role, and nature of thrift crime, analyze factors related to the effectiveness of law enforcement control of savings and loan fraud, and develop the broader implications, from both a theoretical and a policy perspective. Data consist of statistics from various government agencies and focus on all types of thrift, i.e., solvent and insolvent, that fell under the jurisdiction of the Office of Thrift Supervision in Florida, Texas, and California and all insolvent thrifts under the control of the Resolution Trust Corporation (RTC) in Washington, DC. The study focused on Texas, California, and Florida because of the high numbers of savings and loan failures, instances of fraud, and executives being indicted. However, as the study progressed, it became clear that the frauds and failures were nationwide, and while many of the crimes were located in these three states, the individuals involved may have been located elsewhere. Thus, the scope of the study was expanded to provide a national perspective. Parts 1 and 2, Case and Defendant Data, provide information from the Executive Office of United States Attorneys on referrals, investigations, and prosecutions of thrifts, banks, and other financial institutions. Part 1 consists of data about the cases that were prosecuted, the number of institutions victimized, the state in which these occurred, and the seriousness of the offense as indicated by the dollar loss and the number of victims. Part 2 provides information on the defendant's position in the institution (director, officer, employee, borrower, customer, developer, lawyer, or shareholder) and disposition (fines, restitution, prison, probation, or acquittal). The relevant variables associated with the Resolution Trust Corporation (Part 3, Institution Data) describe indictments, convictions, and sentences for all cases in the respective regions, organizational structure and behavior for a single institution, and the estimated loss to the institution. Variables coded are ownership type, charter, home loans, brokered deposits, net worth, number of referrals, number of individuals referred, assets and asset growth, ratio of direct investments to total assets, and total dollar losses due to fraud. For Parts 4 and 5, Texas and California Referral Data, the Office of Thrift Supervision (OTS) provided data for what are called Category I referrals for California and Texas. Part 4 covers Category I referrals for Texas. Variables include the individual's position in the institution, the number of referrals, and the sum of dollar losses from all referrals. Part 5 measures the total dollar losses due to fraud in California, the total number of criminal referrals, and the number of individuals indicted.